Fine motor skills predict expressive, but not receptive, language abilities in minimally verbal autistic adults - Pecukonis, Meredith; Hickey Townsend, Paige; Sarnie, Laura; Jafari, Chakameh; Kosmyna, Nataliya; Protyasha, Nishat; Williamson, James; Yuditskaya, Sophia; Maes, Pattie; Quatieri, Thomas F.; McDougle, Christopher J.; Mody, Maria; et al. (Frontiers in Language Sciences, 2025)
IntroductionPrevious research suggests that the motor system plays an important role in spoken language development for children and adolescents with autism spectrum disorder (ASD). However, no studies to date have examined this association in minimally verbal autistic adults (mvASD) who have limited to no functional use of spoken language.MethodsThe current study investigated the association between fine motor skills and language abilities in a sample of 34 mvASD and 29 neurotypical (NT) adults 18 to 34 years old. More specifically, we examined whether fine motor skills were differentially related to expressive vs. receptive language abilities, and explored whether the identified motor-language associations remained significant when accounting for nonverbal cognitive skills. Fine motor skills were measured using the Grooved Pegboard Test (GPT) and the Beery-Buktenica Developmental Test of Visual Motor Integration, 6th Edition (VMI-6), expressive and receptive language abilities were measured using the Expressive Vocabulary Test, 3rd Edition (EVT-3) and the Peabody Picture Vocabulary Test, 5th Edition (PPVT-5), and nonverbal cognitive skills were measured using the nonverbal subtest of the abbreviated battery of the Stanford-Binet Intelligence Scales (SB-5 Nonverbal).ResultsCorrelation analyses showed that in the mvASD group, fine motor skills were significantly associated with expressive, but not receptive, language abilities. Nonverbal cognitive skills were significantly associated with expressive language abilities and fine motor skills. When all variables were included in a single model, fine motor skills measured by the VMI-6 emerged as the best statistical predictor of expressive language abilities, while nonverbal cognition was the best predictor of receptive language abilities in the mvASD group.DiscussionFindings suggest for mvASD adults, the motor system is involved in expressive language, while broader cognitive systems play a more important role in receptive language. No significant associations were found in the NT group, indicating that the motor-language association commonly found in NT children may decouple in adulthood. Further research is needed to determine whether current findings can be replicated in a larger sample of mvASD adults using longitudinal data.